Pertanggungjawaban Sosial Akuntansi Biru: Studi Pada Perusahaan Perikanan Go-public Di Indonesia - Krestiwanda, Laurentia Julinda Vike; Utami, Intiyas (Owner : Riset dan Jurnal Akuntansi, 2024)
This phenomenon in Indonesia recognizes the importance of fisheries sector companies for society, which has given rise to opinions regarding the form of social responsibility that fisheries companies in Indonesia must carry out. This responsibility is also stated in point number 12 of the SDGs promoted by the UN regarding sustainable consumption and production patterns. This research aims to identify the components of Corporate Social Responsibility (CSR) in fisheries sector companies, especially in the blue accounting aspect. This research method uses qualitative descriptive analysis techniques. The objects used in this research are two fishing companies listed on the Indonesia Stock Exchange. The results of this research support legitimacy theory in accordance with the blue accounting practices of both companies which focus on the social contract between the company and society where companies are required to fulfill society's expectations and demands.